2020
DOI: 10.21203/rs.3.rs-18581/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Failure to replicate the JTC-bias in patients with psychotic disorders: A secondary analysis of a baseline assessment of a randomized controlled trial

Abstract: Background: The jumping to conclusions bias (JTC) is considered to be an important causal factor in theoretical models on the formation and maintenance of delusions. However, recent meta-analytic findings show a rather equivocal pattern of results regarding associations between JTC and delusions. Thus, the aim of the present preregistered study is to investigate in a large sample whether the JTC-bias is more pronounced in patients with psychotic disorders in comparison to controls and whether the JTC bias is a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
2
2
Order By: Relevance
“…Surprisingly, however, we found no group differences for BADE and JTC, contradicting the findings from the bulk of previous work (for a review on BADE, see Eisenacher & Zink, 2017; for a meta-analysis on JTC, see Dudley et al, 2016). Nevertheless, several recent studies also failed to replicate deficits in JTC in psychosis (Pytlik et al, 2020;Moritz et al, 2020). Similar to Pytlik et al (2020), the present study had a 99% power to detect the effect found in Dudley et al (2016) (Hedges g = 0.52), rendering a β-error unlikely.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Surprisingly, however, we found no group differences for BADE and JTC, contradicting the findings from the bulk of previous work (for a review on BADE, see Eisenacher & Zink, 2017; for a meta-analysis on JTC, see Dudley et al, 2016). Nevertheless, several recent studies also failed to replicate deficits in JTC in psychosis (Pytlik et al, 2020;Moritz et al, 2020). Similar to Pytlik et al (2020), the present study had a 99% power to detect the effect found in Dudley et al (2016) (Hedges g = 0.52), rendering a β-error unlikely.…”
Section: Discussioncontrasting
confidence: 86%
“…Nevertheless, several recent studies also failed to replicate deficits in JTC in psychosis (Pytlik et al, 2020;Moritz et al, 2020). Similar to Pytlik et al (2020), the present study had a 99% power to detect the effect found in Dudley et al (2016) (Hedges g = 0.52), rendering a β-error unlikely. Although the reasons for these diverging results remain unclear, both Pytlik et al (2020) and Moritz et al (2020) highlight that the specifics of the paradigms used may offer an explanation.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In this regard, the correlation between DTD and CB as well as the significantly higher CB in subjects who displayed the JTC-bias strongly suggests that this may be the case. On the other hand, recent meta-analyses (30,31) and a large scale study (50), did not find a statistically significant association between the presence of a JTC-bias and delusion severity, although patients with psychotic disorders and delusions presented a more pronounced JTC-bias in comparison to controls. While the correlation between DTD in the fish task and CB was of small effect size (r = -.16), we found a medium effect size (Cohen's d = .53) regarding the group differences between subjects who jumped to conclusions and those who did not.…”
Section: Discussionmentioning
confidence: 86%